Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
This paper investigates the consequences of embedding the Helix-Light-Vortex (HLV) theory's concept of Spiral Time (ψ(t) = t + iφ(t)) into the framework of U(1) gauge theory. We introduce a modified covariant derivative that includes a term for the spiral phase, φ(t), which acts as a dynamic, geometric background. The central finding is a novel mechanism for the quantization of electric charge. We demonstrate that charge quantization emerges naturally as a topological condition—a modified holonomy—derived from the winding properties of the spiral time phase, thus bypassing the need for magnetic monopoles. Additionally, the paper shows how this spiral background induces a structural, non-spontaneous breaking of the global U(1) symmetry while maintaining a generalized form of local gauge invariance. This work provides a unifying perspective that links the fundamental structure of time directly to the origins of gauge symmetry and charge quantization.
This paper investigates the consequences of embedding the Helix-Light-Vortex (HLV) theory's concept of Spiral Time (ψ(t) = t + iφ(t)) into the framework of U(1) gauge theory. We introduce a modified covariant derivative that includes a term for the spiral phase, φ(t), which acts as a dynamic, geometric background. The central finding is a novel mechanism for the quantization of electric charge. We demonstrate that charge quantization emerges naturally as a topological condition—a modified holonomy—derived from the winding properties of the spiral time phase, thus bypassing the need for magnetic monopoles. Additionally, the paper shows how this spiral background induces a structural, non-spontaneous breaking of the global U(1) symmetry while maintaining a generalized form of local gauge invariance. This work provides a unifying perspective that links the fundamental structure of time directly to the origins of gauge symmetry and charge quantization.